METAPHOR OF LOVE AND RELATIONSHIP IN WAVE TO EARTH’S SONG LYRICS - Fitrawati, Fitrawati; Sofian, Nur Israfyan; Arman, Arman (Seshiski: Southeast Journal of Language and Literary Studies, 2024)
This research aims to describe about love and relationship conveyed in Wave to Earth's song lyrics entitled Sunny Days, Light, and Peach Eyes by using the theory of metaphor from Lakoff & Johnson. Lakoff & Johnson implied that metaphor as the domain of experience can be associated with the other expression to explain another one and distributed into three main type name structural, ontological and orientation metaphor. After doing the study, this research finds out eleven lyrics from those three songs by Wave to Earth categorized as metaphor and have the intention to demonstrate how love and relationship showed within the lyrics. From the analysis, the lyrics contain the deep and emotional expression related to love and relationship told in uncommon expression to express how the feeling of the song lyrics.